2015
DOI: 10.1007/s10661-015-4755-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variations of the particulate size distribution and chemical composition over Ibadan, Nigeria

Abstract: Spatial and temporal variation of suspended particulate matter was measured in Ibadan, Nigeria during the raining and dry months of 2013 and 2014, respectively. Six different locations were considered, reflecting city-spread, population density, lifestyle, and vehicular- and industrial-related activities. Elemental characterisation of the samples were carried out using energy dispersive x-ray fluorescence (ED-XRF) spectroscopy, while the black carbon content was determined using an optical transmissometer. Bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 20 publications
2
20
0
1
Order By: Relevance
“…A previous study in Wuhan also reported higher ratios in suburban site (0.64) than urban site (0.57) in 1995(0.57) in -1996(0.57) in (Wei et al, 1999. It was also found the highest PM 2.5 /PM 10 ratio at the control site in Ibadan, Nigeria, because of being far from the road and any obvious source of pollutants (Akinlade et al, 2015).…”
Section: Spatial Disparity Of the Ratiomentioning
confidence: 83%
See 2 more Smart Citations
“…A previous study in Wuhan also reported higher ratios in suburban site (0.64) than urban site (0.57) in 1995(0.57) in -1996(0.57) in (Wei et al, 1999. It was also found the highest PM 2.5 /PM 10 ratio at the control site in Ibadan, Nigeria, because of being far from the road and any obvious source of pollutants (Akinlade et al, 2015).…”
Section: Spatial Disparity Of the Ratiomentioning
confidence: 83%
“…Compared with numerous studies demonstrating the variability of PM concentrations (Eeftens et al, 2012;Hu et al, 2014;Akinlade et al, 2015;Ghim et al, 2015;Huang et al, 2015;Zhang and Cao, 2015;Zhou et al, 2015;Xu et al, 2016a), few studies have reported on the spatio-temporal variability of the PM 2.5 /PM 10 ratio (Blanco-Becerra et al, 2015;Zhang and Cao, 2015;Munir, 2016;Zhou et al, 2016). The goal of this study is to investigate the spatiotemporal variability of the PM 2.5 /PM 10 ratio at a city scale systematically and comprehensively.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The comparison of chemical composition of PM in different typologies of sites in specific areas (such as traffic, industrial, urban, urban background, and rural sites) gives information about the dynamics of airborne particles in the atmosphere and the spatial gradients allowing better distinction of local and distant sources. This allows to distinguish the contributions of local sources from urban and regional backgrounds and from long-range transport (Costa et al, 2016;Akinlade et al, 2015;Pan et al, 2015;Pauraitė et al, 2015;Vodička et al, 2015;Avino et al, 2015;Kaneyasu et al, 2014;Heal and Hammonds, 2014;Dall'Osto et al, 2013;Gianini et al, 2013;Beuck et al, 2011;Arruti et al, 2011;Yin et al, 2010;Guo et al, 2009). This is particularly important in the Mediterranean region that is influenced by air masses coming from Europe, Asia, and Africa (Lelieveld et al, 2002), affected by a large variety of pollution sources (Salameh et al, 2015) and characterized by a complex meteorology, which favors the aging of polluted air masses (Artiñano et al, 2003;Amodio et al, 2012;Contini et al, 2014a;Perrone et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to cities in the developed economies, there is a dominance of the coarse-mode fraction in the atmospheric aerosol loading in major Nigerian cities. This has been attributed to frequent and persistent resuspension of dust from the large expanse of unpaved roads [Akinlade et al, 2015;Obioh et al, 2013;Owoade et al, 2013].…”
Section: 1002/2016jd025584mentioning
confidence: 99%